Evaluating Emotional Outcomes of Medical Students in Pediatric Emergency Medicine Telesimulation - Osamu Nomura; Momoka Sunohara; Ichiro Watanabe; Taichi Itoh (MDPI AG, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has challenged the feasibility of traditional in-person simulation-based clinical training due to the public health recommendation on social distancing. During the pandemic, telesimulation training was implemented to avoid multiple students and faculties gathering in confined spaces. While medical trainees' perceived emotions have been acknowledged as a critical outcome of the in-person simulation-based training, the impact of telesimulation on trainees' emotions has been unexamined. We conducted an educational team-based simulation study with a pediatric case of septic shock. Seventeen and twenty-four medical students participated in the telesimulation training and in-person simulation training, respectively. The institutional pandemic social restrictions at the time of each training session determined the participant assignment to either the telesimulation training or in-person simulation training. All participants responded to the Japanese version of the Medical Emotion Scale, which includes 20 items rated on a five-point Likert-type scale before, during, and after the simulation sessions. The measured emotions were categized into four emotion groups according to two dimensions: positive or negative and activating or deactivating emotions. The one-way analysis of variance between the telesimulation and in-person simulation training revealed no significant differences in the emotions perceived by the participants before, during, and after the simulation training sessions. The perceived emotions of medical students were comparable between the telesimulation and in-person simulation training. Further longitudinal studies with larger samples and multiple variables are needed to generalize the effectiveness of telesimulation.